Alliances for Obesity Prevention: Finding Common Ground: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
Many organizations are making focused efforts to prevent obesity. To achieve their goals, accelerate their progress, and sustain their success, the assistance of many other individuals and groups--not all of them with a singular focus on obesity prevention--will be essential. In October 2011 the Institute of Medicine held a workshop that provided an opportunity for obesity prevention groups to hear from and hold discussions with many of these potential allies in obesity prevention. They explored common ground for joint activities and mutual successes and lessons learned from efforts at aligning diverse groups with goals in common.
Keywords: Food and Nutrition; Health and Medicine

Evaluating Obesity Prevention Efforts: A Plan for Measuring Progress - Institute of Medicine (The National Academies Press, 2013)
Obesity poses one of the greatest public health challenges of the 21st century, creating serious health, economic, and social consequences for individuals and society. Despite acceleration in efforts to characterize, comprehend, and act on this problem, including implementation of preventive interventions, further understanding is needed on the progress and effectiveness of these interventions. Evaluating Obesity Prevention Efforts develops a concise and actionable plan for measuring the nation's progress in obesity prevention efforts—specifically, the success of policy and environmental strategies recommended in the 2012 IOM report Accelerating Progress in Obesity Prevention: Solving the Weight of the Nation. This book offers a framework that will provide guidance for systematic and routine planning, implementation, and evaluation of the advancement of obesity prevention efforts. This framework is for specific use with the goals and strategies from the 2012 report and can be used to assess the progress made in every community and throughout the country, with the ultimate goal of reducing the obesity epidemic. It offers potentially valuable guidance in improving the quality and effect of the actions being implemented. The recommendations of Evaluating Obesity Prevention Efforts focus on efforts to increase the likelihood that actions taken to prevent obesity will be evaluated, that their progress in accelerating the prevention of obesity will be monitored, and that the most promising practices will be widely disseminated.
Keywords: Food and Nutrition; Health and Medicine

Progress in Preventing Childhood Obesity: How Do We Measure Up? - Institute of Medicine (The National Academies Press, 2007)
The remarkable increase in the prevalence of obesity among children and youth in the United States over a relatively short timespan represents one of the defining public health challenges of the 21st century. The country is beginning to recognize childhood obesity as a major public health epidemic that will incur substantial costs to the nation. However, the current level of investment by the public and private sectors still does not match the extent of the problem. There is a substantial underinvestment of resources to adequately address the scope of this obesity crisis. At this early phase in addressing the epidemic, actions have begun on a number of levels to improve the dietary patterns and to increase the physical activity levels of young people. Schools, corporations, youth-related organizations, families, communities, foundations, and government agencies are working to implement a variety of policy changes, new programs, and other interventions. These efforts, however, generally remain fragmented and small in scale. Moreover, the lack of systematic monitoring and evaluation of interventions have hindered the development of an evidence base to identify, apply, and disseminate lessons learned and to support promising efforts to prevent childhood obesity. Progress in Preventing Childhood Obesity: How Do We Measure Up? examines the progress made by obesity prevention initiatives in the United States from 2004 to 2006. This book emphasizes a call to action for key stakeholders and sectors to commit to and demonstrate leadership in childhood obesity prevention, evaluates all policies and programs, monitors their progress, and encourages stakeholders to widely disseminate promising practices. This book will be of interest to federal, state, and local government agencies; educators and schools; public health and health care professionals; private-sector companies and industry trade groups; media; parents; and those involved in implementing community-based programs and consumer advocacy.
Keywords: Health and Medicine

Physical Activity: Moving Toward Obesity Solutions: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
In 2008, the U.S. federal government issued fully approved physical activity guidelines for the first time. The idea that physical activity impacts health can be traced as far back as Hippocrates, and the science around the linkages between physical activity and health has continuously accumulated. On April 14-15, 2015, the Institute of Medicine’s Roundtable on Obesity Solutions held a 2-day workshop to explore the state of the science regarding the impact of physical activity in the prevention and treatment of overweight and obesity and to highlight innovative strategies for promoting physical activity across different segments of the population. This report summarizes the presentations and discussions from this workshop.
Keywords: Food and Nutrition; Health and Medicine

Legal Strategies in Childhood Obesity Prevention: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Since 1980, childhood obesity rates have more than tripled in the United States. Recent data show that almost one-third of children over 2 years of age are already overweight or obese. While the prevalence of childhood obesity appears to have plateaued in recent years, the magnitude of the problem remains unsustainably high and represents an enormous public health concern. All options for addressing the childhood obesity epidemic must therefore be explored. In the United States, legal approaches have successfully reduced other threats to public health, such as the lack of passive restraints in automobiles and the use of tobacco. The question then arises of whether laws, regulations, and litigation can likewise be used to change practices and policies that contribute to obesity. On October 21, 2010, the Institute of Medicine (IOM) held a workshop to bring together stakeholders to discuss the current and future legal strategies aimed at combating childhood obesity. Legal Strategies in Childhood Obesity Prevention summarizes the proceedings of that workshop. The report examines the challenges involved in implementing public health initiatives by using legal strategies to elicit change. It also discusses circumstances in which legal strategies are needed and effective. This workshop was created only to explore the boundaries of potential legal approaches to address childhood obesity, and therefore, does not contain recommendations for the use of such approaches.
Keywords: Food and Nutrition; Health and Medicine

Local Government Actions to Prevent Childhood Obesity - Transportation Research Board; Institute of Medicine; National Research Council (The National Academies Press, 2009)
The prevalence of childhood obesity is so high in the United States that it may reduce the life expectancy of today's generation of children. While parents and other adult caregivers play a fundamental role in teaching children about healthy behaviors, even the most positive efforts can be undermined by local environments that are poorly suited to supporting healthy behaviors. For example, many communities lack ready sources of healthy food choices, such as supermarkets and grocery stores. Or they may not provide safe places for children to walk or play. In such communities, even the most motivated child or adolescent may find it difficult to act in healthy ways. Local governments—with jurisdiction over many aspects of land use, food marketing, community planning, transportation, health and nutrition programs, and other community issues—are ideally positioned to promote behaviors that will help children and adolescents reach and maintain healthy weights. Local Government Actions to Prevent Childhood Obesity presents a number of recommendations that touch on the vital role of government actions on all levels—federal, state, and local—in childhood obesity prevention. The book offers healthy eating and physical activity strategies for local governments to consider, making it an excellent resource for mayors, managers, commissioners, council members, county board members, and administrators.
Keywords: Health and Medicine; Food and Nutrition

Examining a Developmental Approach to Childhood Obesity: The Fetal and Early Childhood Years: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
Recent scientific evidence points to the origins of childhood obesity as an outcome of the dynamic interplay of genetic, behavioral, and environmental factors throughout early development, with a compelling body of evidence suggesting that both maternal and paternal nutritional and other exposures affect a child's risk of later obesity. The burgeoning field of epigenetics has led researchers to speculate that many of the observed associations between early developmental exposures and later risk of childhood obesity are mediated, at least in part, through epigenetic mechanisms. To explore the body of evolving science that examines the nexus of biology, environment, and developmental stage on risk of childhood obesity, the Institute of Medicine and the National Research Council convened a workshop in February 2015. The workshop focused on the prenatal period, infancy, and early childhood and addressed evidence from both animal and human studies. Workshop objectives were to (1) identify epigenetic-mediated relationships between exposure to risk factors during sensitive periods of development (gestation through age 3) and subsequent obesity-related outcomes; (2) explore the science around periods of plasticity and potential reversibility of obesity risk in the context of early childhood development; and (3) examine the translation of epigenetic science to guide early childhood obesity prevention and intervention to reduce obesity risk. This report summarizes the information presented and discussed at the workshop.
Keywords: Food and Nutrition; Health and Medicine

Bridging the Evidence Gap in Obesity Prevention: A Framework to Inform Decision Making - Institute of Medicine (The National Academies Press, 2010)
To battle the obesity epidemic in America, health care professionals and policymakers need relevant, useful data on the effectiveness of obesity prevention policies and programs. Bridging the Evidence Gap in Obesity Prevention identifies a new approach to decision making and research on obesity prevention to use a systems perspective to gain a broader understanding of the context of obesity and the many factors that influence it.
Keywords: Food and Nutrition; Health and Medicine

Measuring Progress in Obesity Prevention: Workshop Report - Institute of Medicine (The National Academies Press, 2012)
Nearly 69 percent of U.S. adults and 32 percent of children are either overweight or obese, creating an annual medical cost burden that may reach $147 billion. Researchers and policy makers are eager to identify improved measures of environmental and policy factors that contribute to obesity prevention. The IOM formed the Committee on Accelerating Progress in Obesity Prevention to review the IOM's past obesity-related recommendations, identify a set of recommendations for future action, and recommend indicators of progress in implementing these actions. The committee held a workshop in March 2011 about how to improve measurement of progress in obesity prevention.
Keywords: Health and Medicine

Accelerating Progress in Obesity Prevention: Solving the Weight of the Nation - Institute of Medicine (The National Academies Press, 2012)
One-third of adults are now obese, and children's obesity rates have climbed from 5 to 17 percent in the past 30 years. The causes of the nation's obesity epidemic are multi-factorial, having much more to do with the absence of sidewalks and the limited availability of healthy and affordable foods than a lack of personal responsibility. The broad societal changes that are needed to prevent obesity will inevitably affect activity and eating environments and settings for all ages. Many aspects of the obesity problem have been identified and discussed; however, there has not been complete agreement on what needs to be done to accelerate progress. Accelerating Progress in Obesity Prevention reviews previous studies and their recommendations and presents five key recommendations to accelerate meaningful change on a societal level during the next decade. The report suggests recommendations and strategies that, independently, can accelerate progress, but urges a systems approach of many strategies working in concert to maximize progress in accelerating obesity prevention. The recommendations in Accelerating Progress in Obesity Prevention include major reforms in access to and opportunities for physical activity; widespread reductions in the availability of unhealthy foods and beverages and increases in access to healthier options at affordable, competitive prices; an overhaul of the messages that surround Americans through marketing and education with respect to physical activity and food consumption; expansion of the obesity prevention support structure provided by health care providers, insurers, and employers; and schools as a major national focal point for obesity prevention. The report calls on all individuals, organizations, agencies, and sectors that do or can influence physical activity and nutrition environments to assess and begin to act on their potential roles as leaders in obesity prevention.
Keywords: Food and Nutrition; Health and Medicine

Educating the Student Body: Taking Physical Activity and Physical Education to School - Institute of Medicine (The National Academies Press, 2013)
Physical inactivity is a key determinant of health across the lifespan. A lack of activity increases the risk of heart disease, colon and breast cancer, diabetes mellitus, hypertension, osteoporosis, anxiety and depression and others diseases. Emerging literature has suggested that in terms of mortality, the global population health burden of physical inactivity approaches that of cigarette smoking. The prevalence and substantial disease risk associated with physical inactivity has been described as a pandemic. The prevalence, health impact, and evidence of changeability all have resulted in calls for action to increase physical activity across the lifespan. In response to the need to find ways to make physical activity a health priority for youth, the Institute of Medicine's Committee on Physical Activity and Physical Education in the School Environment was formed. Its purpose was to review the current status of physical activity and physical education in the school environment, including before, during, and after school, and examine the influences of physical activity and physical education on the short and long term physical, cognitive and brain, and psychosocial health and development of children and adolescents. Educating the Student Body makes recommendations about approaches for strengthening and improving programs and policies for physical activity and physical education in the school environment. This report lays out a set of guiding principles to guide its work on these tasks. These included: recognizing the benefits of instilling life-long physical activity habits in children; the value of using systems thinking in improving physical activity and physical education in the school environment; the recognition of current disparities in opportunities and the need to achieve equity in physical activity and physical education; the importance of considering all types of school environments; the need to take into consideration the diversity of students as recommendations are developed. This report will be of interest to local and national policymakers, school officials, teachers, and the education community, researchers, professional organizations, and parents interested in physical activity, physical education, and health for school-aged children and adolescents.
Keywords: Health and Medicine; Education